An Overview of Islamic Finance - Hussain, Mumtaz (IMF Working Papers; Working Paper ;, 2015)
Islamic finance has started to grow in international finance across the globe, with some concentration in few countries. Nearly 20 percent annual growth of Islamic finance in recent years seems to point to its resilience and broad appeal, partly owing to principles that govern Islamic financial activities, including equity, participation, and ownership. In theory, Islamic finance is resilient to shocks because of its emphasis on risk sharing, limits on excessive risk taking, and strong link to real activities. Empirical evidence on the stability of Islamic banks, however, is so far mixed. While these banks face similar risks as conventional banks do, they are also exposed to idiosyncratic risks, necessitating a tailoring of current risk management practices. The macroeconomic policy implications of the rapid expansion of Islamic finance are far reaching and need careful considerations.